Tinjauan Juridis Perkembangan Tanah-Tanah Adat (Dahulu, Kini dan Akan Datang) - Novyta Uktolseja; Pieter Radjawane (SASI, 2019)
Regarding land acquisition by humans (land tenure), Indonesia has its own history of the occurrence of various complex land tenure categories. Each land tenure category each has a characteristic setting regarding land ownership and ownership, and management objectives. This can be seen in Indonesian society in each area of residence other than the Indonesian people, the land also affects the government which in this case the government has the authority to control the land in use and intended for the community but the fact that the community is at a disadvantage by the government. thus how is the development of customary land which in the past was not registered, then in the present many customary land must be registered if registered so that the status of the land that was originally customary land changed status to property rights, then how to protect land adat which does not register what the impact of these lands will be in the future.